A review on the influence of chemical modification on the performance of adsorbents - Segun Michael Abegunde; Kayode Solomon Idowu; Olorunsola Morayo Adejuwon; Tinuade Adeyemi-Adejolu (Resources, Environment and Sustainability, 2020)
Adsorption is one of the oldest and extensively studied techniques for water and wastewater treatment. As a surface phenomenon, adsorption efficiency relies heavily on the surface chemistry of the natural and modified material. The mode of surface modification and the nature of the precursor have significant impacts on surface functionalities. Chemical method of surface treatment is a technique that alters the structure and the surface properties of the precursor to enhance adsorption process. The present work intends to deliver precise knowledge on the choice and impacts of chemical modification on some known adsorbing materials.